Gender, War, and Religion: Feminist Perspectives on Pathways to Just Peace - Zorgdrager, Heleen (Feminist theology, 2024)
Starting with clashes between Western and Ukrainian feminists, this article discusses basic questions from an intersectional perspective on the relation between gender, war and religion. In the context of Russia’s war against Ukraine, how should a gender-sensitive peace ethics look? Among feminists, as in religious communities, we find radical pacifist positions next to and sometimes conflicting with approaches that draw on traditions of “just war” and/or “just peace.” After discussing the different approaches in Christian tradition, including Eastern traditions, and describing the imperialist nature of the Russian-Ukrainian war, the author highlights the importance of engaging feminist theories of war and militarism in the analysis and how they resonate with practices on the ground in Ukraine. The feminist lens demands attention for the full reality of war, for women’s multilayered agency in war, and for the genderedness of discourses and practices surrounding war heroism and war traumas. Based on such considerations and arguments, the article proposes five “principles” for a feminist political theology on war and peace, as a contribution to the ongoing scholarly debate. Markers on a feminist-theological pathway to just peace may include: reconsidering the notion of sacrifice; fearlessly bringing theology into religious diplomacy; nothing for Ukraine without the voices of Ukrainian women; embracing a paradigm of human security instead of state security; and the remaining challenge to imagine a common future with the enemy beyond the current evil of destruction.